2018
DOI: 10.13057/biodiv/d190501
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation of captive Malayan Gaur (Bos gaurus hubbacki) based on mitochondrial D-loop region DNA sequences

Abstract: Md-Zain BM, Abdul-Aziz A, Aifat NR, Mohd-Yusof NS, Norsyamimi R, Rovie-Ryan JJ, Karuppannan KV, Zulkifli NA, YaakopS. 2018. Sequence variation of captive Malayan Gaur (Bos gaurus hubbacki) based on mitochondrial D-loop region DNA sequences.Biodiversitas 19: 1601-1606. Malayan gaur (Bos gaurus hubbacki) can only be found in Peninsular Malaysia and southern Thailand.The International Union for Conservation of Nature (IUCN) has listed Malayan gaur in the Red List as vulnerable. The main objectiveof this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(27 reference statements)
2
3
0
Order By: Relevance
“…Our result is in line with a recent study which also observed low genetic diversity among gaur populations of Central India based on partial mtDNA D-loop sequences 38 . Similar low mtDNA diversity was also observed in Malayan gaur for partial D-loop sequence 39 . Low mtDNA diversity is likely to occur in the wild population due to the presence of small number of founder females 38 41 .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Our result is in line with a recent study which also observed low genetic diversity among gaur populations of Central India based on partial mtDNA D-loop sequences 38 . Similar low mtDNA diversity was also observed in Malayan gaur for partial D-loop sequence 39 . Low mtDNA diversity is likely to occur in the wild population due to the presence of small number of founder females 38 41 .…”
Section: Resultssupporting
confidence: 80%
“…Similar low mtDNA diversity was also observed in Malayan www.nature.com/scientificreports/ www.nature.com/scientificreports/ gaur for partial D-loop sequence 39 . Low mtDNA diversity is likely to occur in the wild population due to the presence of small number of founder females [38][39][40][41] . Also, it can be taken as a sign of population decline 40,42,43 .…”
Section: Protein Coding Genes (Pcgs)supporting
confidence: 75%
“…Greater sequence variation found in two historical DNA sequences further confirms the loss diversity no longer found in the present-day wild gaur population of MTR. Lack of mitochondrial DNA variation in the current wild gaur population points toward the presence of a single, small population of wild gaur with less number of founder females in MTR (Md-Zain et al 2018). Considering the single locus and contribution of mtDNA to the whole genome, low diversity at the maternal level is justified and reported in several species Khaire et al 2016).…”
Section: Discussionmentioning
confidence: 95%
“…A low genetic diversity in the current study may be assigned to the small population size and repeated introduction of animals from same source over the years. Low mtDNA diversity is likely to occur in the wild population due to the presence of small number of founder females [59][60][61][62]. It has been already stated by [63] that the gaur population is anticipated to fall by 30% within the next three decades due to habitat loss, poaching for its meat and horns, and fatal diseases.…”
Section: Genetic Diversitymentioning
confidence: 99%